O roli autorytetów w turkusowych społecznościach samoorganizujących się zespołów .......... 57 - Blikle, Andrzej (Autorytety w naszym życiu: Nauka – kultura – media, 2025)
ON THE ROLE OF AUTHORITIES IN TEAL COMMUNITIES OF SELF-ORGANIZING TEAMSThe concept of teal organizations, including teal companies, was introduced by Frederic Laloux. The distinguishing feature of these organizations is the lack of management in the traditional sense of the term. In teal organizations, the bosses who tell people who and what to do are replaced by leaders who answer the question “HOW?”. These are the teal authorities who teach and support employees. All operational decisions are made by their later executors. That is why teal organizations are also referred to as self-organizing.